The Dynamics of Succession of Vegetation in the Post-Shifting Cultivation Area in Central Kalimantan - Ardiatma Maulana; Priyono Suryanto; Widiyatno Widiyatno; Eny Faridah; Bambang Suwignyo (Jurnal Ilmu Kehutanan)
Indonesia’s forests is the third largest tropical forest after Brazil and Africa. However, the high rate of forest degradation in Indonesia led this country become one of the most largest contributor of greenhouse gas emissions in the world. One of the causes of the degradation of tropical forest in Indonesia is the shifting cultivation practice. The succession of vegetation after shifting cultivation practice can provide ecological services such as increasing vegetation cover and improving soil properties but takes too long to recover. This study aims to understand the dynamics of vegetation succession in the post-shifting cultivation advanced stage. This study was conducted using systematical nested sampling method to take sample of shurb and herbs, and trees, including, seedling and, sapling growth stage form three different stage of post-shifting cultivation land areas, ie young fallow (1 - 10 years), intermediate fallow (11 - 20 years), old fallow (> 20 years), and natural forest. The vegetation data were then analyzed using Important Value, Species Richness, Diversity and Evenness Indices. Analysis of variance with post-hoc test of DMRT assays was used if the results each vegetation indices differed significantly between stage of post-shifting cultivation land. The Species Richness and Diversity Index of shurb and herb, seedling, sapling, and tree have significantly increased (P < 0,05) except the herb and shrub communities. The Species richness and Diversity Index of tree stage of old fallow were not significantly different from natural forest but it was composed with different species.